Behavioural responses of Anopheles gambiae to standard pyrethroid and PBO-treated bednets of different operational ages - Emma Reid; Frank Mechan; Jeff Jones; Amy Lynd; Janet Hemingway; Philip McCall; David Weetman (Current Research in Parasitology and Vector-Borne Diseases)
To combat pyrethroid insecticide resistance, there has been widespread distribution of pyrethroid-treated bednets (ITNs) co-impregnated with piperonyl butoxide (PBO), a synergist that inhibits enzyme activity to block metabolic resistance. While PBO impacts physiological resistance, mosquito behavioural responses when attempting to blood-feed through nets may be more dependent on net characteristics, in particular the insecticide treatment and operational age of nets. These potentially interacting effects are currently not well characterised. This study aimed to investigate the behavioural responses of Anopheles gambiae to different types of ITNs of different ages to evaluate the relationships between behaviours, insecticide type, age of net and mortality. A pyrethroid-resistant An. gambiae strain originally from Busia, Uganda, was tested with modified WHO cone assays in which a human arm is provided as bait and the trial is video recorded. Using the recordings, movement patterns throughout the cone were monitored to assess net contact and avoidance behaviours. Nets tested were PermaNet 2.0, PermaNet 3.0, Olyset and Olyset Plus, aged 0 months (unused), 12 months, and 25 months post-deployment, all collected from a field trial in Uganda. Our primary hypothesis was that behavioural indices of irritancy would decline with net age as active ingredient concentrations decline, in line with mortality. Knockdown and mortality were highest on baseline nets with PBO and declined thereafter, whereas each was much lower and invariant with age for non-PBO nets. Mosquito movement in the cones was also higher at baseline and declined with age for PBO nets, but not non-PBO nets, indicating an association between mortality and irritancy-induced movement. Baseline nets with PBO also elicited less net contact than older nets, whilst non-PBO nets showed no relationship between net contact and age. PBO nets also elicited irritancy behaviour even after a short period of exposure. In conclusion, the addition of PBO was initially effective in restoring the efficacy of nets, but this relative advantage declined with time, as did the behavioural indices, movement and net contact, suggesting declining irritancy as PBO is lost.